Cybersecurity Awareness and Social Media Reach: Analyzing the Effectiveness of Awareness Content Distribution - E, Mohamed Ismail (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
In today’s digital age, numerous social media platforms exist, yet cybersecurity awareness content posted by government or private organisations often fails to reach a broad audience for various reasons. This project aims to bridge that gap by creating 30 cybercrime awareness videos, each ranging from 2 to 15 minutes in length, and posting them on Facebook, Instagram, and YouTube. Over a period of two weeks or more, we will monitor and assess the reach and engagement of these videos. By documenting the reasons behind their reachability, we can identify key factors that either enhance or inhibit the dissemination of this crucial information. This analysis will enable us to refine our content and format, ensuring that our cybersecurity awareness messages effectively reach and educate the maximum number of people.